Beyond PTSD : helping and healing teens exposed to trauma - Gerson, Ruth, 1981-; Heppell, Patrick, 1980-; American Psychiatric Association Publishing (Washington, DC : American Psychiatric Association Publishing, 2019)
Impulsivity, poor judgment, moodiness, risky behavior. "You don't understand." "I don't care." "Whatever, bro." Engaging and working with teenagers is tough. Typically, we attribute this to the storms of adolescence. But what if some of the particularly problematic behaviors we see in teens -- self-destructive behaviors, academic issues, substance abuse, reluctance to engage in therapy or treatment -- point to unspoken trauma?Teens nationwide struggle with traumatic stress related to poverty, abuse, neglect, bullying, traumatic loss, and interpersonal or community violence. But youth are also generally reluctant to disclose or discuss experiences of traumatic stress, and adults working with these youth may not immediately perceive the connection between prior trauma and the teen's current risky or concerning behavior. Beyond PTSD: Helping and Healing Teens Exposed to Trauma helps adults recognize and understand traumatized youth, and provides concrete strategies for talking to and engaging the teen, overcoming resistance, and finding the most appropriate evidence-based treatment approach for them.Nearly twenty contributors pull from their extensive and varied experience working in schools and hospitals to child welfare programs, juvenile justice facilities, pediatric offices, and with families to provide concrete tips to manage the challenges and opportunities of working with trauma-exposed adolescents. Chapters present trauma-informed approaches to youth with aggression, suicide and self-injury, psychosis, and school refusal; youth with physical or developmental disabilities or medical comorbidities, those in juvenile justice or child welfare; teen parents; and LGBTQ youth, among others. Throughout the text, tables compare different types of trauma therapies and provide information about how treatments might be adapted to fit a specific teen or setting. Readers will also find "real life" case vignettes and concrete, specific clinical pearls -- even examples of language to use -- to demonstrate how to work effectively with difficult-to-engage teens with complex symptoms and behaviors.Written to be practical and accessible for clinicians, social workers, pediatricians, school counselors, and even parents, with the information, context, and strategies they need to help the teen in front of them.
Teens and traumatic stress : a toxic combination / Ruth Gerson -- Recognition and treatment / Patrick Heppell -- Aggression and criminal behavior / Jennifer Cabrera and Jessica Linick -- Suicide and self-injury / Gabrielle Carson -- Risky behavior and substance use / Sophie de Figueiredo and Moises Rodriguez -- School refusal and other academic and behavioral problems in school / Rachel Mandel -- Psychosis and dissociation / Ruth Gerson -- The implications of trauma for sexual and reproductive health in adolescents / Rebecca Weis, Aron Janssen, and Jeremy Wernick -- Trauma and youth with disabilities / Karen Rogers -- Acute psychiatric services / Schuyler Henderson and Blake Phillips -- School systems / Patrick Heppell -- Child welfare and juvenile justice / Patrick Heppell -- Medical providers / Alexis Kant Yetwin -- Families / Fadi Haddad, and Gabrielle Carson -- Improving services for traumatized adolescents through advocacy and systems change / Jeanette Scheid and Cynthia Chu.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 072, 650 - OCLC control number change
Keywords: Post-traumatic stress disorder in adolescence -- Treatment; Teenagers -- Mental health services; Adolescent psychology; Behavior disorders in adolescence; Child welfare; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Stress Disorders, Traumatic; Psychological Trauma -- therapy; Psychology, Adolescent; Dangerous Behavior; Psychosocial Support Systems; Child Welfare; Electronic books